Marketing Strategy, Social Media, and Product Innovation Effects on Loyalty at Kopi Kenangan - Sastra Mico; Elvera Elvera (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: The impact of marketing strategies, social media, and product innovation on customer satisfaction, loyalty, and purchasing decisions, with brand trust serving as an intervening variable in the context of Kopi Kenangan, was examined in this study. Methodology: In this research, a quantitative approach employing the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique was utilized, and the data were analyzed using the SmartPLS 4 application. Data were collected through questionnaires administered to 100 active consumers of Kopi Kenangan. Results: The study found that Brand trust was significantly and positively influenced by marketing strategies, social media, and product innovation. Additionally, brand trust significantly affects consumer satisfaction, loyalty, and purchasing decisions. Conclusions: This study concludes that brand trust plays a central role in enhancing customer satisfaction, loyalty, and purchase decisions. Effective marketing strategies, active social media use, and continuous product innovation are crucial for fostering brand trust and, consequently, boosting consumer behavior. Limitations: The study is limited by its focus on Kopi Kenangan with a sample of 100 respondents, which may not fully represent the broader market. Further studies should expand the sample size and consider other brands for generalizability. Contributions: A theoretical contribution to the understanding of the relationship between marketing strategies, social media, product innovation, and brand trust is provided by this study. Practical insights for businesses seeking to strengthen consumer loyalty and improve purchasing decisions through targeted marketing and innovation strategies are also offered.